General Dielectric Response and A.C. Conductivity - Banerjee, Ananya; Sarkar, A. (Asian Journal of Chemistry, 2011)
A simple non linear form of dielectric response function is proposed. The proposed dielectric response function is an essential extension of Debye linear response. The proposed dielectric response function is a simple one following L-C-R electric analogue of material to depict a non Debye response function. The function of diecectric response is capable to reproduce existing other response function along with some new features. The corresponding form of A.C. electrical conductivity and susceptibility are also extracted. The overall results obtained are good and encouraging.